Micronutrient inadequacy in Europe: the overlooked role of food supplements in health resilience - Christie, Samantha; Crooks, David; Thomson-Selibowitz, Rowena; Green-Woolard, Ashley; Mantantzis, Konstantinos (Frontiers in Nutrition, 2025)
Micronutrient inadequacy is a significant issue in Europe, partly driven by an evolving food landscape. Food supplements play a critical role in offsetting these gaps, particularly in vulnerable groups, and contribute to the overall health resilience, wellbeing, and productivity across the life-course and population. However, both the extent and impact of micronutrient insufficiency and the essential role of food supplements remain underrecognized in public health, clinical training, and practice. We examine the reasons behind this widespread under-acknowledgment, along with selected evidence demonstrating the tangible benefits of food supplements in bridging micronutrient gaps and fostering health resilience. We discuss the health policy implications of incorporating food supplements into public health strategies to enhance nutritional status, help reduce the risk of chronic diseases, improve workforce productivity, and reduce healthcare costs across Europe. Ultimately, we call for an integrated approach to nutrition policy that fully recognizes and utilizes the value of food supplements in supporting a healthier and more resilient European population.